Reducing Work Stress through Employee Engagement: A Randomized Controlled Trial - Khajeh Naeeni, Sepehr; Lobos-Rivera, Marlon Elías; Bhat, Rizwan Hassan (KMAN Counseling & Psychology Nexus, 2024)
This study aimed to evaluate the effectiveness of an Employee Engagement Training Program in reducing work-related stress among employees. The research sought to determine whether structured training could foster employee engagement and alleviate stress, contributing to improved job satisfaction and organizational success. A randomized controlled trial was conducted with 40 full-time employees experiencing mild to moderate work-related stress. Participants were divided into an experimental group, which received the Employee Engagement Training Program, and a control group, which did not receive any intervention. The training consisted of 8 sessions, each lasting 90 minutes, focusing on stress management, communication skills, resilience, and goal setting. Data were analyzed using a two-way Analysis of Variance (ANOVA) with repeated measurements and Bonferroni post-hoc tests. The results demonstrated a significant reduction in perceived work stress levels among participants in the experimental group compared to the control group. Specifically, the experimental group showed a notable decrease in work stress from pre-test to post-test and maintained this reduction at the two-month follow-up. The ANOVA revealed significant effects for time, group, and their interaction on work stress levels, indicating the training program’s effectiveness. The Employee Engagement Training Program significantly reduced work-related stress among participants, underscoring the importance of structured training in enhancing employee engagement and well-being. These findings suggest that organizations can benefit from implementing similar programs to foster a positive work environment, improve job satisfaction, and achieve organizational success. Future research should aim to explore the long-term effects of such interventions and their applicability across different sectors.